2017
DOI: 10.1016/j.juro.2016.08.110
|View full text |Cite
|
Sign up to set email alerts
|

Cause and Effect versus Confounding—Is There a True Association between Caudal Blocks and Tubularized Incised Plate Repair Complications?

Abstract: Our data indicate that hypospadias severity and not the type of regional anesthesia was the only risk factor significantly associated with postoperative complications. To confirm these findings and provide strong and definitive evidence on this topic a well powered, randomized, controlled trial is clearly required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 14 publications
0
34
0
Order By: Relevance
“…Although patient selection for caudal block was based on anesthesiologist discretion, a higher proportion of children with mid-shaft/proximal hypospadias received a caudal block compared with those with distal defects 10. To adjust for this imbalance between the groups and to eliminate potential selection bias involving caudal block indication, we performed subgroup analysis including only patients with distal hypospadias 5 9 10 23 24.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although patient selection for caudal block was based on anesthesiologist discretion, a higher proportion of children with mid-shaft/proximal hypospadias received a caudal block compared with those with distal defects 10. To adjust for this imbalance between the groups and to eliminate potential selection bias involving caudal block indication, we performed subgroup analysis including only patients with distal hypospadias 5 9 10 23 24.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, non-randomized assignment to intervention may occur in observational studies. Which kind of anesthesia (caudal block or DNPB) the patient received was mainly determined by anesthesiologist discretion and patients with severe hypospadias were more likely to receive caudal block and not DNPB 10. This imbalance might introduce bias in measurement classification of interventions and selection bias.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to what they report, our surgeon routinely injected lidocaine with epinephrine in the glans during all repairs except the most minimal glanular cases including those with and without caudal anesthetics. Finally, Braga et al (11) found a statistically significant association between fistula development or glans dehiscence and pre-operative use of testosterone, proximal hypospadias, and use of caudal block on univariate analysis; however, the association was only significant for proximal hypospadias on multivariate analysis. Therefore, they concluded, as did Zaidi et al ,(12) that the association between complications and caudal block was only a confounder and that the severity of the hypospadias was the only predictor of complications.…”
Section: Discussionmentioning
confidence: 97%
“…Conversely, such association was not confirmed by two other studies. (11, 12) There remains a need to answer this important question regarding any association of caudal anesthetic technique and postoperative surgical complications.…”
Section: Introductionmentioning
confidence: 99%
“…There is ongoing controversy whether caudal blocks lead to a higher incidence of urethral fistulas, although the evidence is of poor quality and needs confirmation. 28 …”
Section: Operative Principlesmentioning
confidence: 99%